2021
DOI: 10.5539/gjhs.v13n7p1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID– 19 on the Psychological Health of Dental Professionals: A Systematic Review

Abstract: BACKGROUND: An outbreak of novel coronavirus disease (COVID-19), has influenced every aspect of life. Healthcare workers, especially dentists, are at a high risk of getting infected due to close contact with patients Aim: to identify factors that can affect the psychological health of dental professionals during the COVID – 19 pandemic. METHOD: This systematic review was conducted for the full-text English articles focusing in the field of dentistry, specifically looking at the impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 59 publications
(105 reference statements)
1
8
0
Order By: Relevance
“…According to Mishra et al [29] concern relating to being infected with the COVID-19 contagion was one of the most frequent sources of stress among DHPs in Chhattisgarh, India and further elaborates that dentistry is such a profession that involves working in close proximity to the oral cavity and its secretions, and includes procedures that are aerosol producing is unavoidable in most of the dental procedures due to which the risk of getting infected is heightened thus leading to anxiety and frustrations. Similar findings were made by Gohil et al [30] where fear of contagion, subjective overload, and perceived job insecurity and loss of income are causing distress among the DHPs. Some participant's expressed that COVID has reduced their workload which allowed for some feeling of satisfaction.…”
Section: Discussionsupporting
confidence: 87%
“…According to Mishra et al [29] concern relating to being infected with the COVID-19 contagion was one of the most frequent sources of stress among DHPs in Chhattisgarh, India and further elaborates that dentistry is such a profession that involves working in close proximity to the oral cavity and its secretions, and includes procedures that are aerosol producing is unavoidable in most of the dental procedures due to which the risk of getting infected is heightened thus leading to anxiety and frustrations. Similar findings were made by Gohil et al [30] where fear of contagion, subjective overload, and perceived job insecurity and loss of income are causing distress among the DHPs. Some participant's expressed that COVID has reduced their workload which allowed for some feeling of satisfaction.…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, professionals with insomnia were 13 times more likely to develop depressive symptoms than those without insomnia (39). Increased depression incidence may be associated with a fear of contracting the infection or infecting family members, as has been reported in some studies (33,51). A recent review study examining frontline professionals also indicated an association between depressive symptoms and the direct diagnosis or treatment of COVID-19 patients (5).…”
Section: Discussionmentioning
confidence: 84%
“…The fear of infection ranged from 60 to 96.6% ( N = 12) among dental professionals ( 33 ). Additionally, a prevalence of 77.1% ( N = 4, n = 3,558) for fear of infection was reported in Asia ( 61 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This made routine procedures troublesome in addition to causing enormous stress and anxiety among healthcare workers [3,7]. Anxiety is related to a decrease in the quality and quantity of treatment [8,9] that results in the patients' as well as the practitioner's well-being being compromised [10,11]. Interestingly, several studies concluded that among all professions, dentistry has the highest rate of stress generated [10,[12][13][14], and now, due to COVID-19, the stress levels have been further elevated.…”
Section: Introductionmentioning
confidence: 99%